2007
DOI: 10.1136/emj.2007.048413
|View full text |Cite
|
Sign up to set email alerts
|

Role of brain natriuretic peptide (BNP) in risk stratification of adult syncope

Abstract: Aims: To assess the value of a near-patient brain natriuretic peptide (BNP) test to predict medium term (3 month) serious outcome for adult syncope patients presenting to a UK emergency department (ED). Methods: This was a prospective cohort pilot study. Consecutive patients aged >16 years presenting with syncope over a 3 month period were eligible for prospective enrolment. All patients who were medium or high risk according to our ED's existing syncope guidelines underwent near-patient BNP testing using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In a recent study, assessment of NT-pro-BNP was helpful in differentiating cardiac from non-cardiac syncope 24. In another study, BNP testing showed it to be an independent predictor of adverse outcome in patients with syncope presenting to an ED 25. Further studies are required to define the role of biomarkers in the diagnostic algorithm of syncope in order to improve their sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, assessment of NT-pro-BNP was helpful in differentiating cardiac from non-cardiac syncope 24. In another study, BNP testing showed it to be an independent predictor of adverse outcome in patients with syncope presenting to an ED 25. Further studies are required to define the role of biomarkers in the diagnostic algorithm of syncope in order to improve their sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Based on an earlier pilot study of 100 patients,16 17 we assumed that the study population would have a raised troponin I rate of 10% and that serious outcome or all-cause death would occur in 50% of troponin I-positive patients and 15% of troponin I-negative patients. We calculated that, to detect a difference in outcome with troponin I measurement, we would need 185 patients with 17 serious outcomes or all-cause deaths to have 80% power at p<0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Although BNP was originally used to determine severity and prognosis in heart failure, the development of rapid and inexpensive assays has allowed its role to evolve and expand. It is increasingly being used in the acute setting to differentiate between cardiac and non-cardiac causes of dyspnoea20 and it has been suggested to also play a role in identifying cardiac causes of syncope 21. Studies investigating BNP in the context of endurance events are fewer but do suggest a rise after prolonged exercise 6 8–11 13…”
Section: Introductionmentioning
confidence: 99%